Kajian ke arah merealisasikan jaringan rujukan tegak geodetik baru di negeri Sabah - Aziz, Anual (2005)
A homogenous, uniform and consistent vertical control system is essential for the infrastructural development of a nation. Peninsular Malaysia has an adequate vertical control based on a well-defined vertical datum known as Peninsular Malaysia Geodesy Vertical Datum 1984 (PMGVD84). However, for the state of Sabah, a different scenario exists. The levelling network is not widespread even though the activities concerning heighting control were started as early as 1910. The nature of the topography is the major factor that contributes to this scenario. This thesis presents the results of a research concerning the height control system in Sabah. It also includes the history of existing height control system and the need to establish a new network. Ever since the development of the height control system, mean sea level values as derived from tidal observations at tide gauge stations along Sabah coast are utilise to fulfil the requirement for a local height datum. Levelling operation to connect all tide gauges was carried out by Sabah Land and Survey Department (LSD) and Department of Survey and Mapping Malaysia (JUPEM). Although the method and the level of accuracy of the levelling operation conformed to the first order levelling procedure, no single adjustment and analyses were done. Due to this reason, this research has not only documents the tidal observation and levelling survey activities in Sabah, but has also presents the result of the levelling network adjustment and their analyses. Research shows that the activities carried out by JUPEM in developing the new height control system were well managed and planned. Results from the minimally constraint least square adjustment suggested that Kota Kinabalu tide gauge bench mark, TG2018 is the most suitable height datum for Sabah Geodetic Vertical Reference Network (SGVRN) as defined in Helmert orthometric height system by 1,322 bench mark of Sabah Precise Levelling Network (SPLN). The overall accuracy of any height value in SPLN is given by 1.035mmvK, where K is levelling route distance in kilometre with the maximum estimated standard deviation less than 2cm across the levelling network. Results of the study also suggest that the development of height control network can be successfully derived from tidal observation, precise levelling and gravity data. This homogeneous and comprehensive height control network will lead to an establishment of a new SGVRN that will consequently act as a catalyst to the well planned infrastructural development in Sabah.